2005
DOI: 10.2337/diabetes.54.8.2305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD68 and Macrophage Chemoattractant Protein-1 Genes in Human Adipose and Muscle Tissues

Abstract: To examine the role of adipose-resident macrophages in insulin resistance, we examined the gene expression of CD68, a macrophage marker, along with macrophage chemoattractant protein-1 (MCP-1) in human subcutaneous adipose tissue using real-time RT-PCR. Both CD68 and MCP-1 mRNAs were expressed in human adipose tissue, primarily in the stromal vascular fraction. When measured in the adipose tissue from subjects with normal glucose tolerance, covering a wide range of BMI (21-51 kg/m 2 ) and insulin sensitivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
272
4
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(299 citation statements)
references
References 44 publications
19
272
4
4
Order By: Relevance
“…2A). In accordance with previous reports (3,5,6,26), stromalvascular cells abundantly express MCP1 and CD68 ( Fig. 2B and C), whereas the adipocyte fraction predominantly expresses adiponectin (Fig.…”
Section: G6pd and Inflammatory Signals In Adipocytessupporting
confidence: 78%
“…2A). In accordance with previous reports (3,5,6,26), stromalvascular cells abundantly express MCP1 and CD68 ( Fig. 2B and C), whereas the adipocyte fraction predominantly expresses adiponectin (Fig.…”
Section: G6pd and Inflammatory Signals In Adipocytessupporting
confidence: 78%
“…We performed a partial identification of other stromal cell types involved in AM synthesis. It is known that macrophages, frequently present in adipose tissue (25), produce AM in vitro (16,26). Our results demonstrate that AM and CD 68 proteins were colocalized, strongly suggesting that macrophages within adipose tissue can synthesize AM.…”
Section: Discussionsupporting
confidence: 61%
“…These findings are also consistent with the development of glucose and insulin tolerance being similar in the two strains. In comparison, a human study recently showed that pioglitazone treatment improved insulin sensitivity in subjects with impaired glucose tolerance in association with reductions in MCP-1 and macrophages in subcutaneous adipose tissue, suggesting that these events were related [26]. However, on the basis of our present findings, it now appears likely that pioglitazone may have affected insulin sensitivity, MCP-1 levels and macrophage accrual through different mechanisms.…”
Section: Discussionsupporting
confidence: 58%